Research on the Distribution and Escape Characteristics of Dust at the Blasting Pile in an Open-Pit Mining Area - Yong Cao; Xiaoliang Jiao; Rong Liu; Haoran Wang; Yi He; Jie Chen; Xiang Lu; Huangqing Zhang (Geosciences)
In open-pit mines, substantial amounts of dust are generated at various stages. Due to the long duration, repeated mechanical disturbance, and large volume of material handled during the shoveling and loading of blasting piles, this stage is recognized as one of the primary contributors to overall dust emissions in open-pit mining operations. The objective of this study is to investigate the spatial dispersion characteristics of dust at blasting piles and evaluate the influence of wind direction on dust migration and escape behavior. This study uses a full-scale numerical model to analyze the airflow and dust migration characteristics at blasting piles under different wind directions. Simulation results show that dust particles of different sizes exhibit distinct dispersion patterns: large particles settle near the source, medium particles migrate a moderate distance, and fine particles (PM2.5 and PM10) travel further and are more likely to escape from the pit. The leeward slope and pit bottom are identified as critical zones of dust accumulation and escape. Under both dump-side and stope-side wind conditions, respirable dust (d < 5 μm) accounts for more than 50% of the escaped particles, posing potential health risks to workers. These findings establish a scientific basis for targeted dust suppression strategies, supporting safer and more sustainable mine site management.